2018
DOI: 10.1007/s00253-018-9079-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative persistence of human sewage-specific enterococcal bacteriophages in freshwater and seawater

Abstract: Enterococcus faecalis bacteria have been recently reported for their ability to host bacteriophages that are specifically from human sewage, suggesting their application to track human fecal contamination in water resources. However, little is known about the survivability of sewage-specific enterococcal bacteriophages in various water matrices under ambient and storage conditions. In this study, bacteriophages that were derived from the Thailand-isolated E. faecalis strains AIM06 and SR14 exhibited morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Various experimental designs have been employed to assess the effects of predation and/or competition in aquatic systems. Some studies have allowed discrimination between the effects of protozoa and those of indigenous bacteria (roughly, predation versus competition) via the use of inhibitory compounds (e.g., cycloheximide and various antibiotics) (28,90,122,131,(152)(153)(154)(155)(156)) that affect only one group, while others have excluded all indigenous microbiota by filtration (4,27,28,45,90,102,153,(155)(156)(157)(158)(159)(160)(161), autoclaving (25,101,131,156), or "baking" of sediments (45,122,156), which does not allow comparison of the effects of different protozoa and bacteria but instead evaluates the effect of the total indigenous microbiota.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental designs have been employed to assess the effects of predation and/or competition in aquatic systems. Some studies have allowed discrimination between the effects of protozoa and those of indigenous bacteria (roughly, predation versus competition) via the use of inhibitory compounds (e.g., cycloheximide and various antibiotics) (28,90,122,131,(152)(153)(154)(155)(156)) that affect only one group, while others have excluded all indigenous microbiota by filtration (4,27,28,45,90,102,153,(155)(156)(157)(158)(159)(160)(161), autoclaving (25,101,131,156), or "baking" of sediments (45,122,156), which does not allow comparison of the effects of different protozoa and bacteria but instead evaluates the effect of the total indigenous microbiota.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…Several studies investigated the effect of the indigenous aquatic microbiota on microorganisms other than bacteria (e.g., bacteriophages and C. parvum oocysts) in marine water and freshwater (159,160), albeit with mixed results. While the decay rates of C. parvum were greater in the presence of the indigenous microbiota, suggesting that biotic interactions play a role in its survival (160), the presence of indigenous microbiota increased the decay rates of enterococcal bacteriophages (159), but not somatic and Fϩ coliphages or GB-124, a bacteriophage that infects Bacteroides spp.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…Protective effects of sediments to poliovirus, adenovirus, and F‐specific coliphages were shown, while enhanced inactivation for rotavirus was observed in the same study (Chung & Sobsey, ). Another study demonstrated that suspended solids enhanced inactivation of bacteriophages infecting enterococci by mechanisms other than phage adsorption to suspended solids (Booncharoen et al, ). Even with limited information for crAssphage, it is possible that the CR usp portion in water samples containing high organic matters and suspended solids would have led to higher crAssphage loss, comparing to the CR sp portion with recent spiking of crAssphage stock (i.e., 10 min).…”
Section: Resultsmentioning
confidence: 99%
“…Accurate abundance of crAssphage contamination is necessary for comparison among water samples. Many factors are known to cause losses during laboratory processing of viruses, potentially resulting in lower recovery efficiencies (Booncharoen, Mongkolsuk, & Sirikanchana, ; Mackowiak, Leifels, Hamza, Jurzik, & Wingender, ). Therefore, the spiking method is commonly used for assessing method recovery, typically by adding known amount of viruses to the water sample, prior to measuring and calculating the recovered portion in the final sample compared to the added stock (Hamza et al, ; Stoeckel, Stelzer, & Dick, ).…”
Section: Introductionmentioning
confidence: 99%
“…In natural conditions, however, water often contains organic matter that can reduce the effectiveness of disinfectants. Likewise, organic and inorganic interfering substances have been shown to affect the decay of bacteriophages and viruses in natural water (Booncharoen, Mongkolsuk, & Sirikanchana, ; Oidtmann, Dixon, Way, Joiner, & Bayley, ). Our present study revealed that soiling interference affected the efficacy of most disinfectants, but not Virkon ® .…”
Section: Discussionmentioning
confidence: 99%